TRAINING AND DEVELOPMENT PRACTICES AT FRONTLINE VR SOLUTIONS PVT. LTD. - Sharma, Yash; George, Linu; Sharma, Bhawna (International Journal of Research -GRANTHAALAYAH, 2025)
The paper discusses the T&D practices of Frontline VR Solutions Pvt. Ltd., a technologydriven organization specializing in Virtual Reality and immersive digital services. Based on primary insights gathered during a one-month internship and supported by secondary research, the study investigates HR operational efficiency, recruitment practices, onboarding, documentation processes, and employee skill development within the company. The analysis reveals that there are key strengths in organizational structure, workflow coordination, and HR operations; at the same time, it recognizes that organizational changes would be warranted regarding digitization, structured training modules, enhanced communication, and technology-enabled HR solutions. It concludes by providing practical recommendations toward developing an effective training approach, enhancing employee engagement and HR process optimization. The research paper describes in detail the T&D practices of Frontline VR Solutions Pvt. Ltd., a technology-driven organization specializing in Virtual Reality (VR), Augmented Reality, and immersive digital solutions. This study aims to understand how effectively the T&D processes of the company support employee capability enhancement, HR operational efficiency, and organizational performance. The research is based upon primary observations from a one-month internship experience, combined with secondary literature and organizational insights into HR activities such as recruitment, onboarding, documentation management, attendance tracking, and employee communication.